Finding Letter Game to Improve Early Literacy Skills in 4-5 Year Old Children at Yasmin Preschool, Jember - Wardatun Jamilah; Wasminingsih (Journal of Indonesian Primary School, 2025)
This research aims to improve early literacy skills in children aged 4-5 years at PAUD Yasmin through the use of games. Finding Letter". The action research method was used by involving 15 children (8 girls and 7 boys) at PAUD Yasmin. In the first cycle, the success rate reached 70%, with 4 children who had not yet reached the success criteria. In the second cycle, the success rate increased to 85%, with 2 children still making mistakes in the alphabetical order but achieving the set success rate of 80%. Data was collected through observation, tests, and interviews. Research findings show that the use of games " Finding Letter" significantly improve children's early literacy skills. The implications of these findings emphasize the importance of utilizing educational games to improve early literacy skills in childhood.